The Comparison of Mind Wandering and Cognitive Distortions in Adults with Attention-Deficit Hyperactivity Disorder with and Without Pornography - Sahar Nasrollahi Valojerdi; Abbas Abolghasemi; Reza Soltani Shal (پژوهش‌های کاربردی روانشناختی)
The aim of this study was to evaluate cognitive distortions and mind wandering in college students with attention deficit hyperactivity disorder with and without pornography. The research design was descriptive comparative causal, and it was practical in terms of its purpose. The statistical population of Tehran in 2022 consisted of 2432 students, including 1449 women and 983 men, pornographic students without ADHD symptoms, and students with and without ADHD symptoms. The research sample consisted of 500 adults with ADHD and or without pornography. These individuals were categorized into 4 categories of 125 individuals based on their cutoff scores: 1) with ADHD and pornography, 2) with ADHD and without pornography, 3) without ADHD and pornography, and 4) as usual. The research instruments included the Adult Attention Deficit Hyperactivity Questionnaires (ASRS), Problematic Use of Porn (PPUS-P), Mind Wandering Deliberate and Spontaneous Scales (MWS), and Cognitive Distortions (CDS). The data was analyzed using the spss24 software, which included univariate and multivariate analysis of variance (MANOVA) and the Hochberg GT2 post hoc test. The results showed that there is a distinction among the four categories (p<0.05). The group with ADHD and pornography exhibits a greater degree of mind straying than the group with ADHD and without pornography, and the group without ADHD and with pornography exhibits a greater degree of mind wandering than the normal group. The cognitive distortion of premat​ure conclusions was reduced in the group with ADHD/with pornography and the group with ADHD/without pornography, while the group without ADHD/with pornography scored lower than the normal group in all distortions. Therefore, these findings may be applied to the fields of pathology, prevention, and intervention given the ineffective cognitive patterns and mental wandering observed in individuals with ADHD and porn addicts.